Investigating the impact of El Niño Southern Oscillation and North Atlantic Oscillation on Temperature regime in the Republic of Azerbaijan - Mehdiyev, Tamerlan; Mammadov , Asgar; Nuriyev, Anar (Geographica Pannonica, 2026)
The study aims to investigate recent changes in the climate of Azerbaijan and climate drivers behind these changes. To reveal the combined influences of multiple climate oscillations, it was decided to employ regression models with climate teleconnections of North Atlantic Oscillation (NAO) and El Niño Southern Oscillation (ENSO). Prior to these, Statistical analysis such as Mann – Kendall test and extreme value tests were applied to identify statistically significant trends. The findings revealed that temperature persistence dominates the local climate in the country. Overall, the impact of North Atlantic Oscillation is small, while El Nino – Southern Oscillation shows little to no impact.